2014
DOI: 10.1002/cctc.201402392
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Catalytic Effects in Tri‐Component Mesostructured Ru–Cu–Ce Oxide Nanocomposite in CO Oxidation

Abstract: This work focuses on probing the synergetic catalytic effects in mesostructured tri‐component Ru–Cu–Ce oxides in CO oxidation reaction. The crystallized nanocomposites with RuO2 and CuO nanoparticles dispersed homogeneously in the pore network of mesoporous CeO2 were synthesized by the nanocasting replication method. The greatly enhanced catalytic activity was achieved by CuO incorporating in mesoporous CeO2, and further by RuO2 incorporating in the mesostructure of CuO/CeO2. Two types of synergetic catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The properties of ceria, in turn, are associated with the arrangement of the terminated surface oxygen atoms, which greatly depends on the morphology, structure, and components. Generally, there are two strategies to enhance ceria catalytic activity, including the optimization of ceria morphologies/structures and the combination of ceria with secondary species, such as noble metals or metal oxides, to form composites . For the first strategy, numerous morphologies/structures of ceria have been designed, such as nanorods, nanotubes, nanosheaths, nanobundles, mesoporous, cage bells, and other morphologies/structures .…”
Section: Introductionmentioning
confidence: 99%
“…The properties of ceria, in turn, are associated with the arrangement of the terminated surface oxygen atoms, which greatly depends on the morphology, structure, and components. Generally, there are two strategies to enhance ceria catalytic activity, including the optimization of ceria morphologies/structures and the combination of ceria with secondary species, such as noble metals or metal oxides, to form composites . For the first strategy, numerous morphologies/structures of ceria have been designed, such as nanorods, nanotubes, nanosheaths, nanobundles, mesoporous, cage bells, and other morphologies/structures .…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous literature, the oxide-supported Pt cations can be responsible for the activation of adsorbed CO molecules, weakening Pt–CO bonds, and promoting catalytic activity. , Meanwhile, CO adsorption/activation on oxidized copper species has been reported to be possible as well. Previous reports confirmed that the exposure of CuO–CeO 2 to CO can produce reduced Cu­(I) species, which benefits the CO reactive adsorption and subsequent conversion of CO to CO 2 . As a result, the formation of Pt δ+ –CO and Cu + –CO double active sites in Pt/CuO x –CeO 2 MS composites can simultaneously contribute to the CO molecule adsorption and synergistically facilitate the activation of adsorbed CO, thus greatly enhancing their catalytic activity for CO oxidation reaction. …”
Section: Resultsmentioning
confidence: 77%
“…It is well‐known that SnO 2 possesses abundant active surface deficient oxygen species and its lattice oxygen is reducible, hence a concerted interaction could occur between RuO 2 and SnO 2 to promote the reaction performance . To understand and confirm this effect, the activity of 2 % and 5 % Ru/SiO 2 was also evaluated under the same condition for comparison purpose.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that SnO 2 possesses abundant active surface deficient oxygen species and its lattice oxygen is reducible, hence a concerted interaction could occur between RuO 2 and SnO 2 to promote the reaction performance. [23] To understand and confirm this effect, the activity of 2 % and 5 % Ru/SiO 2 was also evaluated under the same condition for comparison purpose. It is particularly mentioned here that as a rigid support without active oxygen species, SiO 2 lacks the concerted interaction with the supported active components, [24] such as RuO 2 in this study.…”
Section: Activity Evaluationmentioning
confidence: 99%